IMPROVING THE CONSOLIDATION CHARACTERISTICS OF SALINE SABKHA SOIL BY ADDING BITUMEN (Jurnal Teknologi (Sciences & Engineering), 2022)
The rapid economic and population growth, increase in constructions, and a small selection of appropriate soil resources in Kuwait have made it necessary to research soil stabilization methods because the existing soils are currently unsuitable in their natural conditions. In this study, the consolidation characteristics of sabkha soil samples in southern Kuwait mixed with 0%, 4%, 8%, and 10% bitumen with respect to soil dry weight were investigated. For this purpose, an experimental program, including soil characterization tests, modified Proctor compaction test, one-dimensional consolidation test, and collapsibility test, was executed. Results indicate that increasing the bitumen percentage improves the compressibility characteristics of sabkha soil. Upon the addition of 10% bitumen, the yield stress increased from 25 to 34 kPa, compression index slightly increased from 0.02774 to 0.03145, and swelling index decreased from 0.0119 to 0003. Further, there was a considerable reduction in the collapse potential from 1.192 to 0.301 upon the addition of 10% bitumen. Thus, it is evident that the disadvantageous characteristics of sabkha soil can be mitigated. The results support the possibility of recycling the sabkha soil, thereby contributing toward addressing the environmental issues associated with the disposal of excavated sabkha soil.